Development of a practice model for induced lactation in Malaysia - Rahim, Norsyamlina Che Abdul (2021)
Induced lactation is a method of stimulating breast milk production in women who have not undergone pregnancy. In Malaysia, its awareness has progressively increased with the practice of adoption. Therefore, this study aimed to explore the experience of practitioners, women experiencing and undergoing induced lactation and their support persons, and Malaysia's practice model of induced lactation. Data collection took place in five states based on regions in Malaysia [South (Johor), Central (Selangor), North (Penang), East (Kelantan), and East Malaysia (Sabah)] from December 2015 to June 2017. Three approaches were used for this multiple case study, include semi-structured interviews, structured surveys, and document review. The results were presented and described according to the respondents’ characteristics. Data saturation was achieved after interviewing a total of 69 respondents [practitioners (n=23); women (n=23); and support persons (n=23)]. The interviews were consented to, audio-recorded, and transcribed verbatim, followed by identification of emerging themes. The verbatim transcripts were managed using ATLAS.ti 8.0 software. Meanwhile, data from the questionnaires were stored in Microsoft Excel. A descriptive analysis was initially utilized. Three themes raised from practitioners were (i) description of practice; (ii) care plans for clients; and (iii) quality and effective continuity of care for the women, which correlate to a successfully induced lactation. Data analysis also revealed three themes related to women’s decision to induce lactation included (i) main motivation factors for undergoing the induced lactation process; (ii) the key challenges for women during the process of induced lactation; and (iii) the factors affecting successful adoptive breastfeeding. The support person’s perception of induced lactation indicates two themes (i) a positive attitude towards the induced lactation process; and (ii) accepting, learning, and implementing the support role. The online survey distributed for support persons (n=23) showed that the main factors that motivated them was “to achieve mahram status (five times feeding)”. This result was congruent with the thematic analysis. The researcher gathered a record of induced lactation programs in hospitals, case notes, instructional material, breastfeeding modules and related government circulars. Based on study findings and literature searches, a Practice Model of Induced Lactation was recommended to predict the outcome of induced lactation practice in Malaysia. Three basic foundations make up this model are Government Policy, Human Capital, and Equipment. These three foundations are necessary foundations that are believed to be related to each other and influence the induced lactation practice among practitioners, women, and support persons either from a positive or negative perspective. This practice model plays an important role in ensuring the safe and effective implementation of the induced lactation protocol in order to increase the rate of breastfeeding success rate in Malaysia.